Culturally Responsive Teaching: Implications for Educational Justice - Magnus O. Bassey (MDPI AG, 2016)
Educational justice is a major global challenge. In most underdeveloped countries, many students do not have access to education and in most advanced democracies, school attainment and success are still, to a large extent, dependent on a student's social background. However, it has often been argued that social justice is an essential part of teachers' work in a democracy. This article raises an important overriding question: how can we realize the goal of educational justice in the field of teaching? In this essay, I examine culturally responsive teaching as an educational practice and conclude that it is possible to realize educational justice in the field of teaching because in its true implementation, culturally responsive teaching conceptualizes the connection between education and social justice and creates the space needed for discussing social change in society.